Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/bjd.18178
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic epidermis is associated with upregulation of CDK 2 and inhibition of CDK 4 activity

Abstract: Summary Background The cyclin‐dependent kinases (CDKs) CDK2 and CDK4 are involved in regulation of cell‐cycle progression, and psoriasis is characterized by hyperproliferation of basal epidermal cells. CDK inhibitory proteins (CKIs) such as p16INK4A (p16) bind CDK4/6 kinases and prevent their interaction with D‐type cyclins. CKIs such as p21Cip1 (p21) and p27Kip1 (p27) associate with CDK–cyclin complexes and prevent their activation. Objectives To gain insight into the molecular implication of CDK2 and CDK4 ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…We provide evidence that the unphosphorylated form of p21 accumulated in vivo in the nuclear compartment of keratinocytes located in the suprabasal, senescent layers of psoriatic lesions, and this is a typical feature of senescent cells, as recently demonstrated [19]. Interestingly, in line with previous reports, we found that phosphorylated p21 (Ser146) was mainly distributed in the cytoplasm of senescent cells, where it co-localized with IGFBP2 (Figure 8).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We provide evidence that the unphosphorylated form of p21 accumulated in vivo in the nuclear compartment of keratinocytes located in the suprabasal, senescent layers of psoriatic lesions, and this is a typical feature of senescent cells, as recently demonstrated [19]. Interestingly, in line with previous reports, we found that phosphorylated p21 (Ser146) was mainly distributed in the cytoplasm of senescent cells, where it co-localized with IGFBP2 (Figure 8).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with IGFBP2, p16 expression was weakly detectable in the epidermis of distant NLS of psoriatic patients (i), and absent in healthy controls (iv) or in the skin of AD patients (v). In line with a recent in vivo study [19], we found that the number of p21 positive cells progressively increased through the transition from Pre-LS ( Figure 2A, ii) to LS (iii) skin, where p21 localization was mainly observed in the nucleus of keratinocytes of the spinous layers of epidermis ( Figure 2A). p21 staining was undetectable in healthy epidermis (iv), and weakly detected in a low number of keratinocytes within NLS (i) and AD (v) epidermis.…”
Section: Igfbp2 Is Highly Expressed In Vivo In the Senescent Keratinosupporting
confidence: 92%
See 1 more Smart Citation
“…In that same study p27/CDKN1B showed decreased expression in nonlesional epidermis, but, in some cases, immunolabeled nuclei for p27 in the uppermost keratinocytes were also observed [ 30 ]. Another study described that the expression of p27/CDKN1B was increased in the uninvolved skin compared to involved skin based on immunostaining [ 31 ]. In our present study, we detected enhanced nuclear positivity of the p27/CDKN1B in the upper layers of the psoriatic uninvolved epidermis and this nuclear positivity showed a negative correlation with disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…CLOCK/BMAL1 protein complex and PER2 regulate cell cycle checkpoints, whose overexpression is involved in epidermal turnover [ 64 ]. In psoriasis, altered distributions can be seen in cell cycle regulatory proteins, CDK2 and cyclin E expression, which cause hyperproliferation and are upregulated in the upper layers of the epidermis [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%